OPORTUNIDADES AGROINDUSTRIALES EN LA CUENCA DEL PACÍFICO - Bailey, William C. (1997)
Compare the possibilities of New Zealand and Peru in export agriculture and agribusiness, in which both countries have great potential. He considers that, to remain competitive internationally, both countries must stop exporting raw materials and replace them with products with higher added value. It analyzes the situation and the expected evolution of four New Zealand export products: meat, milk and derivatives, venison and kiwi, and argues that the central aspect to take advantage of the challenges and opportunities in agribusiness is to never forget the importance of the consumer and the consumption patterns, as the importance given to products sensitive to the environment is growing. As possible strategies, mention is made of taking advantage of the comparative advantages offered by nature, developing products specifically destined for the export market, protecting natural resources while maintaining the international competitiveness of agribusiness.